Meanings and Linguistic Function: Human Influence upon Words According to the Mustafa Nasif View| صور الدلالات والوظائف اللغوية: الصفة الإنسانية للكلمات عند مصطفى ناصف - Ahmadi Usman Sirathan (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
meanings and function of language and human influence upon words. Themeanings and function of language should be intended to solve problems ofhumanity, which is based on their tradition and culture. Values of humanitysignificantly influence the words of language. The method of research isanalytical method, which analyzing substance and reviewing Mustafa Nasif’sthought related to the correlation between meanings and function of languageand human influence upon the word. The writer refers to all books written byMustafa Nasif and other linguistic contemporary books.